Sustainable development of agro-industrial production: approaches, principles, goals and indicators - A. I. Kostyaev; G. N. Nikonova (Аграрная наука Евро-Северо-Востока)
In the context of increasing external shocks and resource constraints, it remains urgent to clarify theoretical and methodological ideas about the mechanisms of sustainable adaptation of subjects of the agrarian economy to the emerging realities. Despite the significant number of publications on this issue in solving general planetary problems, it is necessary to move from studying issues of sustainable development on a global scale to considering them in a territorial and sectoral aspect. Therefore, the aim of the work was to substantiate methodological approaches to the study of sustainability in the development of agroindustrial production at the regional level, taking into account relevant UN documents, and partially test selected indicators and indicators in relation to the conditions of the Northwest. Based on the analysis of domestic and foreign works, it is concluded that there is a lack of unity of scientific views on the concept of "sustainable development", and that there are studies of agricultural problems without linking them to sustainable development goals, according to UN concepts. The author's definition of sustainable development of agro-industrial production is formulated and it is shown that of the 17 UN Sustainable Development Goals, rural areas and agro-industrial production contribute to six of them. A set of principles aimed at ensuring the sustainability of the dynamics of processes in regional agro-industrial production is proposed. The sustainable development goals for regional agro-industrial production and relevant indicators of their implementation, coordinated with the UN Sustainable Development Goals, are considered. The theoretical and methodological provisions were tested on the materials of the North-West. Using Spearman's rank correlation coefficients, the indicators of the stability of the dynamics of the physical volume of GVA, the growth rate of agricultural production and the region's self-sufficiency in basic foodstuffs were determined. The positive and negative trends in the dynamics of sustainable development of agro-industrial production have been identified.